Balai vernacular : images of the Filipino's private space (Manila : Sentrong Pangkultura ng Pilipinas, Museo ng Kalinangang Pilipino, 1992)
The Sentrong Pangkultura ng Pilipinas has compiled in this book three essays on three major forms of shelter used in the Philippines, which have not been designed by professional architects: the nipa hut, the ethnic house, and the urban shanty. These essays have synthesized the in-depth documentation made by architecture students from all over the country on these houses, emphasizing the architectural form, cultural content, and aesthetics of space of these houses.
Acknowledgments -- Foreword -- Introduction -- The ethnic balai: living in harmony with nature -- Squatters shanties -- The bahay kubo -- Appendices
Keywords: VERNACULAR ARCHITECTURE -- PHILIPPINES; DWELLINGS -- PHILIPPINES; DWELLINGS